2000
DOI: 10.2307/2648158
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Context of Contraceptive Use at First Intercourse

Abstract: Further efforts to understand contraceptive choice among adolescents should focus on relationship features. Research on the decision-making process surrounding contraceptive use may benefit from treating this as a partner decision and not just as a decision made by one member of the couple. Further research examining the qualities of the relationship may provide important clues for understanding adolescent contraceptive choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
227
3
19

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(263 citation statements)
references
References 13 publications
14
227
3
19
Order By: Relevance
“…Among the men, stable partnership was positively associated with the use of contraceptives within the three situations investigated. Studies undertaken in other contexts, involving youth in North America 8 and Switzerland, 10 also indicate less frequent use of contraceptives during the first experience of sexual intercourse when this occurred within a casual relationship.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the men, stable partnership was positively associated with the use of contraceptives within the three situations investigated. Studies undertaken in other contexts, involving youth in North America 8 and Switzerland, 10 also indicate less frequent use of contraceptives during the first experience of sexual intercourse when this occurred within a casual relationship.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, upon establishing this type of partnership, women tend to opt for oral contraceptives or other methods instead of male condoms. 2,8 Significant associations were found between the use of contraception by men and being able to count on the family as a potential source of contraceptive methods (probably the male condom). The same association was not verified among the women.…”
Section: Discussionmentioning
confidence: 99%
“…Among adoles-cents in the Add Health study, being in a romantic relationship increased the likelihood of sexual activity (Dittus & Jaccard, 2000). Finally, three-quarters of female National Survey of Family Growth (NSFG) participants aged 25 and under who had their fi rst voluntary sexual intercourse before age 18 said they were "going steady" (73.9 percent) with or engaged to (1.9 percent) their fi rst sexual partner 1 (Manning, Longmore, & Giordano, 2000).…”
Section: Romantic Partnersmentioning
confidence: 99%
“…Past research has shown the importance of relationship characteristics in infl uencing contraceptive use at fi rst intercourse (Manning, Longmore, & Giordano, 2000); for example, female NSFG respondents younger than 18 whose partners were six or more years older were less likely to report contraceptive use at last intercourse than young women whose partners were within two years of their age; they were also more likely to become pregnant and bear a child (Darroch, Landry, & Oslak, 1999). Future research should examine the role of partners more fully.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…In addition, differences in partners' educational attainment appear to affect the likelihood that a nonmarital pregnancy leads to marriage (Testa et al, 1989). Age differences and both partners' educational attainment also appear to affect contraceptive usage, further suggesting the importance of examining the role of both women's and men's characteristics in nonmarital pregnancy (Forste and Morgan, 1998;Manning, Longmore, and Giordano, 2000).…”
Section: Does It Take Two? the Effect Of Partners' Characteristics Onmentioning
confidence: 99%